A standardized nomenclature and atlas of the male terminalia of Drosophila melanogaster. Issue 1 (2nd October 2019) - Rice, Gavin; David, Jean R.; Kamimura, Yoshitaka; Masly, John P.; Mcgregor, Alistair P.; Nagy, Olga; Noselli, Stéphane; Nunes, Maria Daniela Santos; O'Grady, Patrick; Sánchez-Herrero, Ernesto; Siegal, Mark L.; Toda, Masanori J.; et al.
ABSTRACT: Animal terminalia represent some of the most diverse and rapidly evolving structures in the animal kingdom, and for this reason have been a mainstay in the taxonomic description of species. The terminalia of Drosophila melanogaster, with its wide range of experimental tools, have recently become the focus of increased interest in the fields of development, evolution, and behavior. However, studies from different disciplines have often used discrepant terminologies for the same anatomical structures. Consequently, the terminology of genital parts has become a barrier to integrating results from different fields, rendering it difficult to determine what parts are being referenced. We formed a consortium of researchers studying the genitalia of D. melanogaster to help establish a set of naming conventions. Here, we present a detailed visual anatomy of male genital parts, including a list of synonymous terms, and suggest practices to avoid confusion when referring to anatomical parts in future studies. The goal of this effort is to facilitate interdisciplinary communication and help newcomers orient themselves within the exciting field of Drosophila genitalia.